ANALISIS KEKELIRUAN SISWA SMK NEGERI DI KOTA CIMAHI DALAM MENYELESAIKAN SOAL GEOMETRI TRANSFORMASI - Fitri Indah Maulani; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to examine the errors of XI grade students of the State Vocational High School in the city of Cimahi in solving transformation geometry problems. This research was conducted at SMK Negeri 1 Cimahi and the samples were taken as much as 1 class. The number of subjects in this study were 32 students. The research approach used is qualitative with descriptive methods. The data collection technique used was a test instrument. The test instrument used in this research is the National Examination (UN) questions on the transformation geometry material as many as 8 questions that have been validated. The results showed that the XI grade students of State Vocational High School in Cimahi City had errors in solving  transformation geometry problems. Problem number 2 is the most difficult problem with the question indicator calculating the image if it is rotated 270 ° with the center p (a, b), the average percentage is 3%, which means that only 1 out of 32 students answered correctly and many students had errors.